Cultural racism and resistance -revisiting post-reunification Germany in Pepe Danquart’s short film “Schwarzfahrer” (blackrider) (2024)
The tram ride of a young Blackman in post-reunification metropolitan and multicultural Berlin is enmeshed in a cultural racist encounter that problematizes contemporary Germanforeigner/ migrant relations. Deploying cultural racism and resistance as conceptual framework, and using historical-interpretive and textual analysis, the study examines interacting sociocultural- cum-political factors and race theorization implicit in the historical contexts of Germanforeigner/ migrant relations in post-reunification Germany as portrayed in the film. The study concludes that an enduring and deeply set fear of losses of racial identity, people and country escalated the economic, social, and political problems linked to German reunification and induced racial conflict relations that pittedthe native white-German majority against a foreigner/migrant minority – relations yet to fade away in Germany today.